Effects of a monetary union on a small peripheral country: stabilization and competitiveness in Portugal - Castro, Henrique Moreira da Silva Oliveira (2013)
A Work Project, presented as part of the requirements for the Award of a Masters Degree in Economics from the NOVA – School of Business and Economics